PENGARUH DOSIS LARUTAN VITAMIN B KOMPLEKS SEBAGAI BAHAN PENYEMPROTAN TELUR ITIK TEGAL TERHADAP FERTILITAS, SUSUT TETAS, DAYA TETAS, DAN KEMATIAN EMBRIO - Fitria Maghfiroh; Tintin Kurtini; Khaira Nova (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
This research aims to 1) the effect of spraying a solution of  B complex on fertility, weight loss, hatchability, and embryo mortality on eggs of tegal duck;  2) the optimal dose of solution B complex as an ingredient sprayers on fertility, weight loss, hatchability, and embryo mortality on eggs of tegal duck.  This research was conducted at duck farms in the village Bumirestu, District Palas, South Lampung regency in April--May 2015.  Completely rndomized design (CRD) with 4 treatment dose of vitamin B complex (0, 4, 6, and 8 g/l of water) used as spraying and 5 replications. Each experimental unit using  6  eggs of tegal duck. The data were analyzed using ANOVA with  the assumptions of variance at 5% significance level. Significantly different result further tested with orthogonal polynomials test.  The research showed that 1) spraying a solution of vitamin B complex 0--8 g/l of water provide no real effect (P> 0.05) on fertility, hatchability, and embryo mortality.  However, significant (P <0.05) on weight loss; 2) the optimal dose of vitamin B complex use solution 0--8 g/l of water as spraying material tegal duck hatching eggs is 3,9 g/l of water on weight loss. Keywords: vitamin B complex, duck eggs tegal, ferlility, weight loss, hatchability, and embryo mortality.